Perlindungan Hukum Bagi Para Pihak Dalam PerjanjianJual Beli Tanah Yang Sertifikatnya Masih DalamProses Pemecahan Sertifikat - Romadhon, Muhammad Bilal Kurnia; , Darsono, S.H., M.H; , Shalman Al-Farizi. S.H., M.Kn (2016)
The purpose of this study is to analyze the legal consequences of the cancellation of the deed of binding sale and purchase of land and legal protection for the parties in the implementation of the binding sale and purchase of land. This research includes normative legal research. The results showed that: First, the agreement binding sale and purchase of land was made in the form of a notarial deed which is an authentic act and have the force of law is strong, so that if the buyer to cancel the binding agreement of sale and purchase of land, the legal consequences are pengendaan fines and agreements considered to have ended; Second, as a treaty binding the land purchase agreement valid as law for those who make it. Therefore, if one of the parties in default in the binding sale and purchase agreement for example, if the buyer does not meet the payment, as has been requested and agreed to the binding agreement of sale and purchase rights to land are considered null and usually the seller will not returns the money already paid.